Periprosthetic Infection: the Role of the Perioperative Nurse - Howard-Hill, Amelia (Operating Room Nurses Association of Canada Journal, 2018)
The incidence of periprosthetic joint infection and the impact on patients and the health system is substantial due to significant patient morbidity and mortality. A systematic review of the current literature by Christchurch surgeons resulted in the development of an algorithm to outline the current best practice for diagnosis and management of periprosthetic joint infection (Ailabouni, Jennings, & Hooper, 2015). The algorithm and the role of the perioperative nurse in the management of patients with periprosthetic joint infection is discussed. Total joint arthroplasty demand is increasing worldwide, with projections from the USA suggesting that by the year 2030 the demand for total hip arthroplasty (THA) and total knee arthroplasty (TKA) will have increased in that country by 174 per cent and 673 per cent respectively (Kutz, Ong, Lau, Mowat, & Halpern, 2007). Within New Zealand a similar pattern is predicted, with increases by 2030 of 110 per cent and 260 per cent for THA and TKA (Hooper, Lee, Rothwell, & Frampton, 2014). The percentage of revision procedures has changed very little over the last decade with about six per cent of primary implants revised after five years and 12 per cent after ten years (Labek, Thaler, Janda, Argreiter, & Stockl, 2011). Although the percentage of revision procedures remains static, the absolute numbers are increasing due to the increased numbers of primary arthroplasty (Ailabouni, Jennings, & Hooper, 2015). Surgical site infections are a big problem and are the second most commonly reported healthcare associated infection (World Health Organisation (WHO), 2011). Infection is the most common cause of failure in TKA and the third most common cause of failure in THA (Bozic et al., 2009; Bozic et al., 2010). Revision arthroplasty for infection is associated with a five times greater mortality at five years than revision arthroplasty for aseptic loosening (Zmistowski, Karam, & Durinka, 2013). The estimated cost for an infected revision procedure is about four times that of a primary arthroplasty (Dreghorn & Hamblin, 1989; Klouche, Sarali, & Mamoudy, 2010). Failure to adequately diagnose infection in its early stages or treat appropriately will lead to further interventions which increase the overall cost and also result in an inferior functional outcome for the patient.